Temperature and mineral dust variability recorded in two low-accumulation Alpine ice cores over the last millennium - Bohleber, Pascal; Hoffmann, Helene (Climate of the past, 2018)
Among ice core drilling sites in the European Alps, Colle Gnifetti (CG) is the only non-temperate glacier to offer climate records dating back at least 1000 years. This unique long-term archive is the result of an exceptionally low net accumulation driven by wind erosion and rapid annual layer thinning. However, the full exploitation of the CG time series has been hampered by considerable dating uncertainties and the seasonal summer bias in snow preservation. Using a new core drilled in 2013 we extend annual layer counting, for the first time at CG, over the last 1000 years and add additional constraints to the resulting age scale from radiocarbon dating. Based on this improved age scale, and using a multi-core approach with a neighbouring ice core, we explore the time series of stable water isotopes and the mineral dust proxies Ca2+ and insoluble particles. Also in our latest ice core we face the already known limitation to the quantitative use of the stable isotope variability based on a high and potentially non-stationary isotope/temperature sensitivity at CG. Decadal trends in Ca2+ reveal substantial agreement with instrumental temperature and are explored here as a potential site-specific supplement to the isotope-based temperature reconstruction. The observed coupling between temperature and Ca2+ trends likely results from snow preservation effects and the advection of dust-rich air masses coinciding with warm temperatures. We find that if calibrated against instrumental data, the Ca2+-based temperature reconstruction is in robust agreement with the latest proxy-based summer temperature reconstruction, including a Little Ice Age cold period as well as a medieval climate anomaly. Part of the medieval climate period around AD1100-1200 clearly stands out through an increased occurrence of dust events, potentially resulting from a relative increase in meridional flow and/or dry conditions over the Mediterranean.
Gesehen am 13.04.2018